Enrichment of amyloidogenesis at an air-water interface. - Jean, L; Lee, C; Vaux, D (2012)
The aggregation of proteins or peptides into amyloid fibrils is a hallmark of protein misfolding diseases (e.g., Alzheimer's disease) and is under intense investigation. Many of the experiments performed are in vitro in nature and the samples under study are ordinarily exposed to diverse interfaces, e.g., the container wall and air. This naturally raises the question of how important interfacial effects are to amyloidogenesis. Indeed, it has already been recognized that many amyloid-forming peptides are surface-active. Moreover, it has recently been demonstrated that the presence of a hydrophobic interface can promote amyloid fibrillization, although the underlying mechanism is still unclear. Here, we combine theory, surface property measurements, and amyloid fibrillogenesis assays on islet amyloid polypeptide and amyloid-β peptide to demonstrate why, at experimentally relevant concentrations, the surface activity of the amyloid-forming peptides leads to enriched fibrillization at an air-water interface. Our findings indicate that the key that links these two seemingly different phenomena is the surface-active nature of the amyloid-forming species, which renders the surface concentration much higher than the corresponding critical fibrillar concentration. This subsequently leads to a substantial increase in fibrillization.